Circulating angiopoietin-like protein 2 levels and mortality risk in patients receiving maintenance hemodialysis: a prospective cohort study. Issue 5 (16th December 2019) - Morinaga, Jun; Kakuma, Tatsuyuki; Fukami, Hirotaka; Hayata, Manabu; Uchimura, Kohei; Mizumoto, Teruhiko; Kakizoe, Yutaka; Miyoshi, Taku; Shiraishi, Naoki; Adachi, Masataka; Izumi, Yuichiro; Kuwabara, Takashige; et al.
Abstract: Background: Patients undergoing hemodialysis treatment have a poor prognosis, as many develop premature aging. Systemic inflammatory conditions often underlie premature aging phenotypes in uremic patients. We investigated whether angiopoietin-like protein 2 (ANGPTL 2), a factor that accelerates the progression of aging-related and noninfectious inflammatory diseases, was associated with increased mortality risk in hemodialysis patients. Methods: We conducted a multicenter prospective cohort study of 412 patients receiving maintenance hemodialysis and evaluated the relationship between circulating ANGPTL2 levels and the risk for all-cause mortality. Circulating ANGPTL2 levels were log-transformed to correct for skewed distribution and analyzed as a continuous variable. Results: Of 412 patients, 395 were included for statistical analysis. Time-to-event data analysis showed high circulating ANGPTL2 levels were associated with an increased risk for all-cause mortality after adjustment for age, sex, hemodialysis vintage, nutritional status, metabolic parameters and circulating high-sensitivity C-reactive protein levels hazard ratio [HR] 2.04 [95% confidence interval (CI) 1.10–3.77]. High circulating ANGPTL2 levels were also strongly associated with an increased mortality risk, particularly in patients with a relatively benign prognostic profile [HR 3.06 (95% CI 1.86–5.03)]. Furthermore, the relationship between circulating ANGPTL2 levels and mortality risk was particularly strong in patients showing few aging-related phenotypes, such as younger patients [HR 7.99 (95% CI 3.55–18.01)], patients with a short hemodialysis vintage [HR 3.99 (95% CI 2.85–5.58)] and nondiabetic patients [HR 5.15 (95% CI 3.19–8.32)]. Conclusion: We conclude that circulating ANGPTL2 levels are positively associated with mortality risk in patients receiving maintenance hemodialysis and that ANGPTL2 could be a unique marker for the progression of premature aging and subsequent mortality risk in uremic patients, except those with significant aging-related phenotypes.